An Evolutionarily Conserved Transcriptional Activator-Repressor Module Controls Expression of Genes for D-Galacturonic Acid Utilization in Aspergillus niger. Issue 1 (1st January 2017) - Niu, Jing; Alazi, Ebru; Reid, Ian D; Arentshorst, Mark; Punt, Peter J; Visser, Jaap; Tsang, Adrian; Ram, Arthur F J
Abstract: The expression of genes encoding extracellular polymer-degrading enzymes and the metabolic pathways required for carbon utilization in fungi are tightly controlled. The control is mediated by transcription factors that are activated by the presence of specific inducers, which are often monomers or monomeric derivatives of the polymers. A D-galacturonic acid-specific transcription factor named GaaR was recently identified and shown to be an activator for the expression of genes involved in galacturonic acid utilization in Botrytis cinerea and Aspergillus niger . Using a forward genetic screen, we isolated A. niger mutants that constitutively express GaaR-controlled genes. Reasoning that mutations in the gaaR gene would lead to a constitutively activated transcription factor, the gaaR gene in 11 of the constitutive mutants was sequenced, but no mutations in gaaR were found. Full genome sequencing of five constitutive mutants revealed allelic mutations in one particular gene encoding a previously uncharacterized protein (NRRL3_08194). The protein encoded by NRRL3_08194 shows homology to the repressor of the quinate utilization pathway identified previously in Neurospora crassa (qa-1S) and Aspergillus nidulans (QutR). Deletion of NRRL3_08194 in combination with RNA-seq analysis showed that the NRRL3_08194 deletion mutant constitutively expresses genes involved in galacturonic acid utilization. Interestingly, NRRL3_08194 is located next to gaaR (NRRL3_08195) in the genome. The homology to the quinate repressor, the chromosomal clustering, and the constitutive phenotype of the isolated mutants suggest that NRRL3_08194 is likely to encode a repressor, which we name GaaX. The GaaR–GaaX module and its chromosomal organization is conserved among ascomycetes filamentous fungi, resembling the quinate utilization activator-repressor module in amino acid sequence and chromosomal organization.